INVESTIGATING INFAQ INTENTION AMONG MUSLIMS: THE MODERATING ROLE OF COIN-BOX-BASED FUNDRAISING ON ALTRUISM AND RELIGIOSITY - Ita Kika Fauziah (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to examine whether coin-box-based fundraising moderates the influence of altruistic behavior and religiosity on the community's interest in giving infaq (voluntary Islamic donations). The object of this study was the Muslim community of Bone Regency. This research employed a field research design using a quantitative approach. The data analysis technique utilized was Structural Equation Modeling (SEM), operated through the SMART-PLS program.The findings reveal that the altruistic behavior variable has a P-value of 0.756, indicating that it does not significantly influence the interest in giving infaq among the Muslim community of Bone Regency. In contrast, religiosity has a positive and significant effect on the interest in giving infaq, with a P-value of 0.014. Furthermore, coin-box-based fundraising is unable to moderate the relationship between altruism and interest in giving infaq, as indicated by a P-value of 0.696. Likewise, it does not provide a moderating effect on the relationship between religiosity and the interest in giving infaq among the Muslim community of Bone Regency, with a P-value of 0.377.